Molecular characterization of the meq gene of Marek's disease viruses detected in unvaccinated backyard chickens reveals the circulation of low- and high-virulence strains. (9th March 2019) - Mescolini, Giulia; Lupini, Caterina; Felice, Viviana; Guerrini, Alessandro; Silveira, Flavio; Cecchinato, Mattia; Catelli, Elena
ABSTRACT: Marek's disease (MD) is an important lymphoproliferative disease of chickens, caused by Gallid alphaherpesvirus 2 (GaHV-2). Outbreaks are commonly reported in commercial flocks, but also in backyard chickens. Whereas the molecular characteristics of GaHV-2 strains from the commercial poultry sector have been reported, no recent data are available for the rural sector. To fill this gap, 19 GaHV-2 strains detected in 19 Italian backyard chicken flocks during suspected MD outbreaks were molecularly characterized through an analysis of the meq gene, the major GaHV-2 oncogene. The number of four consecutive prolines (PPPP) within the proline-rich repeats of the Meq transactivation domain, the proline content, and the presence of amino acid (aa) substitutions were determined. Phylogenetic analysis was performed using the Maximum Likelihood method. Sequence analysis revealed a heterogeneous population of GaHV-2 strains circulating in Italian backyard flocks. Seven strains, detected from birds affected by classical MD, showed a unique meq isoform of 418 aa with a very high number of PPPP motifs. Molecular and clinical features are suggestive of a low oncogenic potential of these strains. The remaining 12 strains, detected from flocks experiencing acute MD, transient paralysis, or sudden death, had shorter Meq protein isoforms (298 or 339 aa) with a lower number of PPPP motifs and point mutations interrupting PPPP. These features allow us to assert the high virulence of these strains. These findings reveal the circulation of low- and high-virulence GaHV-2 strains in the Italian rural sector.